On the Role of the HBP1 Transcription Factor in Epileptogenesis. - Malone, Taylor J. (Tufts Archival Research Center, 2014)
Abstract: Epilepsy is a disease that is characterized by increased neural activity resulting in recurrent seizures. The development of epilepsy occurs during a period of gradual brain alterations called epileptogenesis, which can result from a precipitating event such as head trauma or an initial seizure event called status epilepticus (SE) or it can occur naturally due to genetic predisposition. Our lab previously identified a correlation between epileptogenesis after chemically induced SE and increased Wnt signaling in the hippocampus, a primary region implicated in temporal lobe epilepsies. The additional observation that expression of HBP1, a Wnt repressor, decreased during this period led us to hypothesize that HBP1 may be a causal agent in epileptogenesis. A literature search revealed a gene block containing HBP1 and eight other genes that when deleted was significantly correlated with increased chance of developing seizures. We created an HBP1 knockout strain of mice, compared its phenotype to that of the clinical patients, and found that the mouse model preserved the increased seizure susceptibility, incomplete penetrance, and development of spontaneous seizures. This data suggests that an HBP1 deletion might be the cause of seizures in these patients. To test if this model could be extended further, we looked at the molecular pathways altered in the knockout mice and found that both the mTor and Wnt signaling pathways were upregulated, which is consistent with alterations observed during epileptogenesis in models of temporal lobe epilepsies. If further investigation reveals that this model is in fact a more general model for epilepsy, it can be used to aid in both the treatment and diagnosis of temporal lobe epilepsies.